(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Politics has traditionally always been associated with the domination of men. With the coming up of the globalization and liberalization era, it has been understood that for any genuine democracy to function, equal participation of women in all spheres of life is of utmost importance. Political participation of women is an essential condition to achieve gender equality. This paper tries to analyze the representation of women in both the houses of Indian Parliament. It discusses the reasons for their low participation and what steps need to be taken to improve the situation. This paper also highlights how countries governed by women tend to perform better in all the social and economic platforms.